Physical fitness and anthropometric profile of mixed martial arts athletes - Bruno Ferreira Marinho; Fabrício Boscolo Del Vecchio; Emerson Franchini (Universidad de León, 2012)
Objective: The aim of this study was to identify the physical fitness and anthropometric profile of mixed martial arts (MMA) athletes and the correlations between these variables. Subjects and methods: Thirteen male MMA athletes (30 ± 4 years-old) participated in this study. They were submitted to anthropometric measurements and the following tests: adapted flexitest, sit-ups, push-ups, long jump, flexed arm hang, 1RM bench press and squat. Results: Main results are as follows: body mass (kg): 82.1 ± 10.9; body fat (%): 11.87 ± 5.11; flexibility (score): 18.38 ± 4.07; sit-ups (rep): 43 ± 11; push-ups (rep): 41 ± 9; long jump (m): 2.19 ± 0.25; flexed arm hang (s): 34 ± 11, 1RM bench- press (kg): 76 ± 23; 1RM squat (kg): 73 ± 15. Furthermore we observed results showed significant correlations between anthropometric variables and physical fitness: body fat and long jump (R = -0.75); body fat and flexed arm hang (R= -0.67); height and squat 1RM (R = 0.67); arm circumference and bench press 1RM (R = 0.77). Conclusion: MMA athletes involved in this investigation have showed poor neuromuscular performance. Body fat was negatively correlated with both power and strength endurance performance, while arm circumference was positively related to upper body maximum strength.